2003
DOI: 10.1002/ppul.10305
|View full text |Cite
|
Sign up to set email alerts
|

Asthma mortality in the Danish child population: risk factors and causes of asthma death

Abstract: Child death due to asthma is a rare and potentially preventable event. We investigated possible risk factors for death due to asthma in children and adolescents, as a step towards preventing or minimizing asthma death in this age group, and improving asthma management and care. We reviewed all 108 cases of asthma death in 1-19-year-olds in Denmark, 1973-1994. Copies of death certificates, hospital records, information from general practitioners, and autopsy records were obtained. The information was assessed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 7 publications
0
24
0
3
Order By: Relevance
“…These characteristics have been reported by others as well. 3,4,6,9 An important observation was that non-sanitized homes and (active or passive) smoking were not uncommon, in spite of the fact that patients, parents, and physicians may be assumed to be aware that these constitute risk factors for worsening of asthma and for SAA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These characteristics have been reported by others as well. 3,4,6,9 An important observation was that non-sanitized homes and (active or passive) smoking were not uncommon, in spite of the fact that patients, parents, and physicians may be assumed to be aware that these constitute risk factors for worsening of asthma and for SAA.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11] All these variables were extracted from the medical records. Data from the period prior to the PICU admission were considered as the baseline values for variables that could potentially change over time (eg, smoking, pets, hay fever).…”
Section: Matching Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5] A number of previous studies from different parts of the world have also reported on risk factors contributing to asthma deaths. [6][7][8][9][10][11][12][13] The aim of this observational study was to identify risk factors contributing to asthma deaths in children during a 6-year study period (2001)(2002)(2003)(2004)(2005)(2006). The Eastern Region population is approximately 5.5 million, 22% of whom (1,276,000) are children below the age of 18 years.…”
Section: Introductionmentioning
confidence: 99%
“…Alguns autores argumentam que a exacerbação é a varável mais importante, porque constitui o maior risco para os pacientes, são um motivo de ansiedade para os pacientes e suas famílias, resultam em maior pressão sobre os profissionais da saúde, além de gerar o maior custo para o sistema de saúde (Lane et al, 2006). As exacerbações são reconhecidas como uma manifestação clínica comum em pacientes com asma grave e são conhecidos por aumentar o risco de mortalidade por asma (Jorgensen et al, 2003). Surpreendentemente, apenas durante os últimos 10 anos as exacerbações têm sido usadas como uma variável primária na investigação sobre eficácia de drogas no tratamento da asma (Pauwels et al, 1997;Reddel et al, 2009 do exercício regular para reduzir as a exacerbações em pacientes asmáticos.…”
Section: Efeito Do Condicionamento Físico No Controle Clínicounclassified